The Therapeutic Effects of QihaPingchuan Capsule in Combination with Triple Therapy (ICS+LABA+LAMA) on Chronic Obstructive Pulmonary Disease - Dong, Zhijun; Dong, Shujiang; Li, Jiang; Zhu, Yanli; Ma, Zhiyong; Hou, Yupei; Zhao, Weidong (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives To explore the curative effect of QihaPingchuan Capsule combined with triple therapy [Inhaled Corticosteroid (ICS)+Long-Acting β2 receptor Agonist (LABA)+Long-Acting Anticholinergic drug (LAMA)] on Chronic Obstructive Pulmonary Disease (COPD). Materials and Methods A total of 92 patients with COPD admitted to the hospital were enrolled between January 2021 and October 2022. According to the random number table method, they were divided into Group A and Group B, with 46 cases in each group. Group B was given routine symptomatic treatment and triple therapy, while Group A was additionally treated with Qiha Pingchuan Capsules. All were treated for two weeks. The clinical curative effect, scores of TCM syndromes and COPD Assessment Test (CAT), 6-Minute Walk Distance (6MWD), Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), Peak Expiratory Flow (PEF), Partial Pressure of Oxygen (PO2), partial Pressure of Carbon dioxide (PCO2), serum C-Reactive Protein (CRP), Interleukin-8 (IL-8) and incidence of adverse reactions were compared between the two groups before and after treatment. Results The total response rate of treatment in group A was significantly higher than in group B (89.13% vs. 71.74%, p <0.05). After treatment, TCM syndromes and CAT scores in group A were significantly lower than those in group B and 6MWD was significantly longer than in group B (p <0.05). FCV, FEV1 and PEF in group A were significantly higher than in group B (p <0.05). PO2 in group A was significantly higher than in group B, while PCO2, CRP and IL-8 levels were significantly lower than those in group B (p <0.05). There was no significant difference in the incidence of adverse reactions between group A and group B (15.22% vs. 10.87%, p >0.05). Conclusion QihaPingchuan Capsule combined with triple therapy (ICS+LABA+LAMA) can improve the clinical curative effect, effectively relieve clinical symptoms and improve pulmonary function and inflammatory response in COPD patients, with reasonable safety.
Keywords: QihaPingchuan Capsule; Inhaled glucocorticoid; Long-acting β2 receptor agonist; Long-acting anticholinergic drug; Chronic obstructive pulmonary disease; Pulmonary function